Risk Factors for Bile Duct Injury in Laparoscopic Cholecystectomy: A Systematic Review - Yohanes Windu Tiar Prakosa; Radian Adhiputra Antonius (Lembaga Pengembangan Kinerja Dosen, 2026)
“Laparoscopic cholecystectomy is the gold standard for treating benign gallbladder disease; however, it is associated with a higher incidence of bile duct injury compared to open cholecystectomy. Bile duct injury is a serious iatrogenic complication that contributes to significant morbidity and mortality, making the identification of comprehensive risk factors essential for effective prevention. This study synthesizes recent evidence on risk factors for bile duct injury in laparoscopic cholecystectomy using a systematic review approach, categorizing risks based on patient, disease, operator, and institutional factors. The review followed PRISMA 2020 guidelines with systematic searches of five electronic databases. Observational studies published in English between 2021 and 2025 involving adult patients were included. Data extraction and quality assessment were independently performed by two reviewers using the Newcastle-Ottawa Scale. Ten studies involving 308,053 patients met inclusion criteria. Fibrotic gallbladder showed the strongest association (OR 166.6), followed by age ≥80 years (OR 3.29), gallbladder wall thickness ≥4–5 mm (OR 0.074), and history of acute cholecystitis (OR 0.038). Failure to achieve the Critical View of Safety and anatomical variations, including hepatic duct trifurcation, were key risks. Prevention requires preoperative scoring, strict adherence to the Critical View of Safety, and referral of complex cases to specialized centers.”